Mouse d-Amino-Acid Oxidase: Distribution and Physiological Substrates - Koga, Reiko; Miyoshi, Yurika; Sakaue, Hiroaki; Hamase, Kenji; Konno, Ryuichi (Frontiers in Molecular Biosciences, 2017)
D-Amino-acid oxidase (DAO) catalyzes the oxidative deamination of D-amino acids. DAO is present in a wide variety of organisms and has important roles. Here, we review the distribution and physiological substrates of mouse DAO. Mouse DAO is present in the kidney, brain, and spinal cord, like DAOs in other mammals. However, in contrast to other animals, it is not present in the mouse liver. Recently, DAO has been detected in the neutrophils, retina, and small intestine in mice. To determine the physiological substrates of mouse DAO, mutant mice lacking DAO activity are helpful. As DAO has wide substrate specificity and degrades various D-amino acids, many D-amino acids accumulate in the tissues and body fluids of the mutant mice. These amino acids are D-methionine, D-alanine, D-serine, D-leucine, D-proline, D-phenylalanine, D-tyrosine, and D-citrulline. Even in wild-type mice, administration of DAO inhibitors elevates D-serine levels in the plasma and brain. Among the above D-amino acids, the main physiological substrates of mouse DAO are D-alanine and D-serine. These two D-amino acids are most abundant in the tissues and body fluids of mice. D-Alanine derives from bacteria and produces bactericidal reactive oxygen species by the action of DAO. D-Serine is synthesized by serine racemase and is present especially in the central nervous system, where it serves as a neuromodulator. DAO is responsible for the metabolism of D-serine. Since DAO has been implicated in the etiology of neuropsychiatric diseases, mouse DAO has been used as a representative model. Recent reports, however, suggest that mouse DAO is different from human DAO with respect to important properties.